Development of technology of centrifugal electroslag casting - A. G. Janishevskaja (Литьë и металлургия, 2002)
In this article there is described the process of slugs production by the method of centrifugal electroslag casting. There is presented the developed the mathematical kinetics model of interaction of metal, slag and gas at electroslag casting at all stages of technological process — from burning-off to crystallization of casting in mode. There are given the optimal parameters of the process and chemical composition ofthe offered slag skull.